Helium turbines design and room temperature testing of a 500 W at 4.5 K refrigerator. (April 2019) - Fu, B; Zhang, Q Y; Chen, S X; Li, S S
Abstract: The indigenous design and development of helium turbines of a 500 W / 4.5 K refrigerator have been started at the Institute of Plasma Physics, Chinese Academy of Sciences. This paper briefly discusses the design process and some of the fabrication drawings for the whole helium refrigerator with two helium turbines, which include the turbine wheel, nozzle, diffuser, shaft, brake compressor, two types of bearing, appropriate housing and all other parts. The helium turbines have been designed, manufactured and tested at room temperature. At room temperature, the test results are acceptable; the shaft vibration amplitude is less than 0.010 mm below 247 krpm. The low temperature testing will be carried out in the future.